Cyclical Unemployment: Sectoral Shifts or Aggregate Disturbances? - Abraham, Katharine G.; Katz, Lawrence F. (Journal of Political Economy, 1986)
Recent work by David Lilien has argued that the positive correlation between the dispersion of employment growth rates across sectors (σ) and the unemployment rate implies that sectoral shifts in labor demand are responsible for a substantial fraction of cyclical variation in unemployment. This paper demonstrates that, under empirically satisfied conditions, traditional single-factor business-cycle models will produce a positive correlation between σ and the unemployment rate. Information on the job vacancy rate permits one to distinguish between a pure sectoral shift and a pure aggregate demand interpretation of this positive correlation. The finding that σ and the volume of help wanted advertising (a job vacancy proxy) are negatively related supports an aggregate demand interpretation.